1961
DOI: 10.1002/gj.3350020207
|View full text |Cite
|
Sign up to set email alerts
|

The late‐glacial climate of North‐West England

Abstract: SUMMARYThe combination of geological and botanical evidence with meteorological reasoning leads to the conclusion that i n the ninth millenium B.C. s m a l l glaciers became re-established in corries and in the heads of the wetter Lake District valIeys, and also in a number of Pennine comes n o d of Bowland Forest. The meteorological factors giving rise to their distribution and comparative extent are discussed. It is inferred that the amount and distribution of precipitation during this episode resembled that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
0

Year Published

1976
1976
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 31 publications
2
71
0
Order By: Relevance
“…Furthermore, the technique fails to take into account variations in valley morphology, which would affect the area~levation distribution of a glacier. To this end, Manley (1959) suggested that, for glaciers whose valleys narrow markedly in their lower reaches, the ELA is three-fifths of the vertical distance up the glacier from the terminal moraine. Finally, the term "backwall elevation", which can have a variety of meanings from the outset, becomes difficult to define for valley glaciers that head in compound cirques.…”
Section: Median Elevationmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the technique fails to take into account variations in valley morphology, which would affect the area~levation distribution of a glacier. To this end, Manley (1959) suggested that, for glaciers whose valleys narrow markedly in their lower reaches, the ELA is three-fifths of the vertical distance up the glacier from the terminal moraine. Finally, the term "backwall elevation", which can have a variety of meanings from the outset, becomes difficult to define for valley glaciers that head in compound cirques.…”
Section: Median Elevationmentioning
confidence: 99%
“…Since the late nineteenth century in Europe, the median elevations of former glaciers have been used to estimate ELAs (Manley, 1959;0strem, 1966). The same technique has been employed by Richmond (1965) and Meierding (1982) in the United States.…”
Section: Median Elevationmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 7, the 535 cirques mea sured in the Rocky Mountains demonstrate a high degree of systematic variability in the length/height ratio, but the mean values (which vary from 1.7 to 5.07 with most values from 2.5 to 3.3) for each range fall within the limits suggested 'by Manley (1959) . These values show that cirques develop toward an optimum vertical shape, despite wide variation in climatic, geomorphic, and geologic environments.…”
Section: Gradientmentioning
confidence: 66%
“…Manley (1959) claimed that a well-developed cirque exhibits a length/height ratio of 2.8 to 3.2, and Embleton and King (1968) demonstrated this for cirques of widely varying sizes. Andrews (1965) found ratios of 2.1 to be common in Labrador, but Embleton and King (1968) suggested that the cirques there are not fully developed.…”
Section: Gradientmentioning
confidence: 98%